Does salt stress constrain spatial distribution of dune building grasses Ammophila arenaria and Elytrichia juncea on the beach?. Issue 18 (8th August 2017) - van Puijenbroek, Marinka E. B.; Teichmann, Corry; Meijdam, Noortje; Oliveras, Imma; Berendse, Frank; Limpens, Juul
Abstract: Rising sea levels threaten coastal safety by increasing the risk of flooding. Coastal dunes provide a natural form of coastal protection. Understanding drivers that constrain early development of dunes is necessary to assess whether dune development may keep pace with sea‐level rise. In this study, we explored to what extent salt stress experienced by dune building plant species constrains their spatial distribution at the Dutch sandy coast. We conducted a field transplantation experiment and a glasshouse experiment with two dune building grasses Ammophila arenaria and Elytrigia juncea . In the field, we measured salinity and monitored growth of transplanted grasses in four vegetation zones: (I) nonvegetated beach, (II) E. juncea occurring, (III) both species co‐occurring, and (IV) A. arenaria dominant. In the glasshouse, we subjected the two species to six soil salinity treatments, with and without salt spray. We monitored biomass, photosynthesis, leaf sodium, and nutrient concentrations over a growing season. The vegetation zones were weakly associated with summer soil salinity; zone I and II were significantly more saline than zones III and IV. Ammophila arenaria performed equally (zone II) or better (zones III, IV) than E. juncea, suggesting soil salinity did not limit species performance. Both species showed severe winter mortality. In the glasshouse, A. arenaria biomass decreased linearly with soil salinity, presumably as a result of osmotic stress. Elytrigia juncea showed a nonlinear response to soil salinity with an optimum at 0.75% soil salinity. Our findings suggest that soil salinity stress either takes place in winter, or that development of vegetated dunes is less sensitive to soil salinity than hitherto expected. Abstract : Our result shows that in the field, soil salinity did not explain the growth of Ammophila arenaria and Elytrichia juncea over a summer period. In the field, both species showed severe winter mortality. In the glasshouse, A. arenaria biomass decreased linearly with soil salinity, presumably as a result of osmotic stress. E. juncea showed a nonlinear response to soil salinity with an optimum at 0.75% soil salinity. Our findings suggest that soil salinity stress either takes place in winter, or that development of vegetated dunes is less sensitive to soil salinity than hitherto expected.